Pelatihan Pengelolaan Desa Wisata Dukuh Penaban di Kabupaten Karangasem - Woro Susianti; Dewa Ayu Made Lily Dianasari; Ni Made Tirtawati; Hanugerah Kristiono Liestiandre; Ida Bagus Putra Negarayana; Luh Nyoman Tri Lilasari; I Gede Made Sukariyanto; Dewa Ayu Nyoman Aridayanti (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2023)
The Dukuh Penaban Traditional Village was the chosen location for community service in the Tourism Management Study Program because in Dukuh Penaban there has not been good governance in terms of developing a tourist village. There are still some conditions where local people are not ready to provide services for tourists who come, because there is no clear management system. This community service is therefore, carried out in the form of Tourism Village Management Training, with participants from all stakeholders in the Dukuh Penaban Tourism Village. The outputs of this activity are: The increase of public understanding of the tourism village governance system, the formation of a tourism governance system managed by a professional management agency in the Dukuh Penaban Traditional Village area that accommodates the aspirations of the local community, as well as the increase of community capability in providing excellent service for tourists, thus making Dukuh Penaban a favorite destination in Karangasem Regency. It is highly expected that this activity will provide benefits in the form of increasing human resources from the Dukuh Penaban Tourism Village who are skilled and independent in managing tourism potential in their area in a sustainable manner.